Safety and Efficacy of Hydroxyurea in Pediatric Sickle Cell Disease: A Comprehensive Systematic Review - Hadia, Dr. Rajesh (Asian Journal of Pharmaceutics (AJP), 2023)
Sickle cell disease (SCD) is a global health concern, particularly in regions with a high prevalence like Africa and India. SCD leads to complications across various organ systems. Hydroxyurea (HU) is a primary treatment option that can mitigate complications. This study assesses the safety and efficacy of HU in pediatric SCD patients, potentially improving their quality of life and guiding clinical practice. This research undertook an extensive examination of the safety and effectiveness of HU in the treatment of SCD among pediatric patients, spanning the years from 2000 to 2022. Multiple databases, including PubMed, Scopus, and the Cochrane Library, were meticulously searched for relevant articles and studies. Rigorous selection criteria focused on pediatric SCD-related research, encompassing clinical trials, observational studies, and systematic reviews. Data extraction followed structured forms and predefined checklists to ensure consistency and transparency. The analysis involved assessing the safety and efficacy-related parameters and factors incidence considering diverse populations. Quantitative values synthesized findings for a comprehensive evaluation. This extensive review encompassed 125 references and identified 37 unique articles examining HU’s safety and efficacy in pediatric SCD patients. The average dosage was 20.9 mg/kg/day, with study durations ranging from 6 months to 27 years. HU significantly reduced painful crises by 46.3%, increased hemoglobin (Hb) and fetal Hb levels, and decreased leukocyte counts, signifying reduced inflammation. Neutropenia was observed as a common adverse drug reaction due to HU therapy. No specific frequency was mentioned in different studies. Importantly, HU improved patients’ quality of life and reduced healthcare utilization. This assessment emphasizes the capacity of HU to mitigate painful crises, decrease complications associated with SCD, and improve the overall quality of life for individuals affected by the condition, irrespective of age or particular SCD subcategories. While these findings offer promise for wider HU adoption, they underscore the importance of vigilant monitoring and personalized treatment plans. The evidence presented supports HU’s transformative role in the care of SCD patients, emphasizing its pivotal role in alleviating the challenges posed by this debilitating condition and the need for ongoing research and optimized clinical implementation.